PENILAIAN KINERJA PEGAWAI DI PEMERINTAH KOTA YOGYAKARTA - Lena Satlita; Yanuardi Yanuardi; Marita Ahdiyana (NATAPRAJA, 2015)
This research aims to describe the performance appraisal of Yogyakarta government employees as well as enabling and inhibiting factors in the assessment of employee performance in Yogyakarta government. This qualitative descriptive research shows there are two performance appraisals in the government of Yogyakarta namely Employee Performance Assessment and Job Performance Assessment government employee. Employee Performance Assessment carried out 2 times a year, in June and December and the performance appraisal only once a year. Assessment methods used in employee performance assessment is a method 360 degrees. Constraints in the evaluation of employee performance assessment is at fault understanding of the guidelines for the implementation of performance appraisal, lack of clear job description in job analysis make it difficult for employees to put it in the assessment and the absence of stylists executive staffing in evaluation of employee performance and timing issues assessment by the employer because constrained by other activity.Key Words: Performance Appraisal, Assessment Indicators, Government Employees of Yogyakarta.